DOES MEANING MATTER MORE THAN TUNE? (The adult learners’ perceptions on the application of Taylor Swift’s song in EFL context) - Edy Supriyanto; Galuh Fitriana Sakti; Mahyati Mahyati; Albertus Krisna Prihasdha; Aam Alamsyah; Novita Sari Dwi (ITScience (Information Technology and Science), 2026)
Song efficacy in EFL and the figurative language in songs have both been widely researched, especially among students of letters. This study examined figurative language in a popular Taylor Swift song and its application in the EFL context. It focused on students’ perceptions of using English songs in their EFL programs, whether the lyrics motivate adult students to learn more, and their perceptions of using Taylor Swift’s song (Eldest Daughter) in EFL learning. The study used a qualitative method to identify students’ perceptions regarding the use of English songs and figurative language in EFL learning. It involved 26 participants, mainly fourth- and fifth-semester English department students, who had attended an English adult EFL program. Using two instruments and triangulation, the study ensured valid findings. The main findings showed that, while students found English songs to be an effective alternative in EFL activities, most preferred songs with topics relevant to their personal learning objectives. The specific use of a Taylor Swift song ('Eldest Daughter') was seen as less relevant to their cultural backgrounds.